Current State of Precision Medicine in Primary Systemic Vasculitides - Demirkaya, Erkan; Arici, Zehra Serap; Romano, Micol; Berard, Roberta Audrey; Aksentijevich, Ivona (Frontiers in Immunology, 2019)
Precision medicine (PM) is an emerging data-driven health care approach that integrates phenotypic, genomic, epigenetic and environmental factors unique to an individual. The goal of precision medicine is to facilitate diagnosis, predict effective therapy and to avoid adverse reactions specific for each patient. The forefront of precision medicine is in oncology, nonetheless it is developing in other fields of medicine including rheumatology. Recent studies on elucidating the genetic architecture of polygenic and monogenic rheumatological diseases have made precision medicine possible by enabling physicians to customize medical treatment through the incorporation of clinical features and genetic data. For complex inflammatory disorders the prevailing paradigm is that disease susceptibility is due to additive effects of common reduced-penetrance gene variants and environmental factors. Efforts have been made to calculate cumulative genetic risk score (GRS) and to relate specific susceptibility alleles for use of target therapies. The discovery of rare patients with single-gene high-pentrance mutations informed on our understanding of pathways driving systemic inflammation. Here, we review the advances in practicing precision medicine in patients with primary systemic vasculitides (PSVs). We summarize recent genetic studies and discuss current knowledge on the contribution of epigenetic factors and extracellular vesicles (EVs) in disease progression and treatment response. Implementation of precision medicine in PSVs is a developing field that will require analysis of a large cohort of patients to validate data from genomics, transcriptomics, metabolomics, proteomics, and epigenomics studies for accurate disease profiling. This multi-omics approach to study disease pathogeneses should ultimately provide a powerful tool for stratification of patients to receive tailored optimal therapies and for monitoring their disease activity.